2010
DOI: 10.1097/mca.0b013e328333f50d
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of myeloperoxidase in coronary artery disease: comparison of unstable and stable angina patients

Abstract: Elevated MPO levels among the ACS patients suggest that this marker may participate in plaque vulnerability and instability process, whereas higher CRP levels were predictive of cardiac events only among the stable angina patients. These findings suggest distinct role of the inflammatory markers studied in the pathophysiology of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 62 publications
0
28
0
2
Order By: Relevance
“…20,23 Furthermore, a significant correlation was revealed between HNP skin deposition and the severity of coronary artery diseases, as evaluated by the number of blood vessels associated with focal lesions and stenosis. 25 We demonstrated that HNPs may act not only as a biomarker like MPO to predict coronary diseases, as previously reported, 42 but also function as an effector to induce or deteriorate inflammatory cardiac events by inducing endothelium-monocyte interaction through increasing the conventional receptor-ligand interaction between ICAM-1 and CD11b, oxidative stress and foam cell formation. In a previous study, we also showed that the stimulation of HUVECs with HNPs dose-dependently increases COX-2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…20,23 Furthermore, a significant correlation was revealed between HNP skin deposition and the severity of coronary artery diseases, as evaluated by the number of blood vessels associated with focal lesions and stenosis. 25 We demonstrated that HNPs may act not only as a biomarker like MPO to predict coronary diseases, as previously reported, 42 but also function as an effector to induce or deteriorate inflammatory cardiac events by inducing endothelium-monocyte interaction through increasing the conventional receptor-ligand interaction between ICAM-1 and CD11b, oxidative stress and foam cell formation. In a previous study, we also showed that the stimulation of HUVECs with HNPs dose-dependently increases COX-2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Morrow et al reported elevated baseline MPO in patients presenting with non-ST elevation ACS to be associated with a higher risk of non-fatal MI or recurrent ACS within 30 days, and inclusion of MPO with B-type natriuretic peptide and cardiac troponin to improve short-term risk assessment and patient stratification [111]. Moreover, MPO was observed to be an independent predictor of MACEs in ACS patients during hospitalization [112].…”
Section: Utility Of Mpo To Predict Major Adverse Coronary Events (Maces)mentioning
confidence: 99%
“…Among patients with ACS, baseline MPO level was an independent predictor of major adverse cardiac events during hospitalization Not given [112] Tang et al…”
Section: Length Of Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Roman et al (46) found that elevated MPO levels were higher in patients with ACS than in patients with stable angina. Also, among patients with ACS, an elevated MPO level (higher than the median value) at admission to the emergency was a predictor of cardiovascular events (death, recurrent angina, congestive heart failure, severe arrhythmia) during hospital stay (OR 2.95, 95% CI, 1.1-8.2).…”
Section: Myeloperoxidase and Acute Coronary Syndromementioning
confidence: 98%